Jurnal BUSINESS & ENTREPRENEURSHIP: Innovation strategu to improve the competitiveness of micro, small, and medium enterprises of Bandar Lampung Banana chips - Hartami dewi, Muhammad Syamsul maarif; Titi Candra sunarti (SB-IPB, 2017)
inovasi dibutuhkan oleh usaha mikro, kecil dan menengah untuk tumbuh dan berkembang menjadi usaha besar.